PENGARUH PEMANFAATAN ALAT PERMAINAN OUTDOOR TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN - Elena Himma Nizrina; Laily Rosidah; Kristiana Maryani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
The gross motoric skill is an ability to use large muscles of arms and legs which are largely needed the coordination of all parts of the child’s body. The every child should have some types of the gross motoric skill which are very useful for his/her further development and growth. The types of movement are three: non locomotoric movements, loco-motoric movements, and manipulative movements. The outdoor game tools can be the learning media to enable the child development and learning simultaneously and comprehensively, especially physical motoric development and learning. In line with this thought, this research has been conducted. This research was aimed to know the effect of the utilities of the outdoor game tools toward the children’s gross motoric skills of 4-5 years old. This research was conducted in 12 Early Childhood Education Schools located in Serang Village, Serang Municipality, Banten Province. As for the research method of researcher is quantitative research with survey. The population of the research involved are some 215 children and 68 children as its sample. The research instrument used in this study are three: questionnaires, interview guide and documentation. The quantitative data analysis was using Microsoft Excel.The research finding shows that the average result of the children gross motoric skill is 21.12 indicating significant effect (21,12 e” 1,658), which means that the utilities of the outdoor game tools towards the gross motoric ability of the 4-5 years old children in 12 Early Childhood Education School in Serang Village are very useful to develop further all aspect of the children physical motoric, particularly their gross motoric skills.